Settlement Of Divorce Cases Caused By Domestic Violence In The Palembang Religious Court (Ruling Number 280/Pdt.G/2022/Pa.Plg) - Pratama, Rendy William Cahya; Zainuddin, Cholidi; Zahri, Saipudin (Universitas Labuhanbatu, 2024)
Marriage is a marriage carried out based on statutory regulations and religious teachings. Every person in this world certainly wants to have a family with the person they love, leave a legacy to continue the family lineage, and continue to protect their religion and country. Everyone dreams of a happy marriage full of love that can only end in death. The test must be done at home, so it must be done at your own pace. The current problem is domestic violence, which leads to deteriorating marital relations and divorce. The research used is empirical and legal research. And it includes the resolution of divorce cases based on domestic violence at the Palembang Religious Court (Decision No. 280/Pdt.G/2022/Pa.Plg). Findings: The process for resolving domestic divorce cases at the Palembang Religious Court is the same as the process for resolving other divorce cases, there are only slight differences. If the form of domestic violence is psychological, the evidence provided is in the form of a doctor's certificate, but in cases of physical violence, the evidence provided is not only in writing but must also be through statements from witnesses and victims. The process of resolving cases in court must use a trial agenda: reading of the complaint, mediation, answers and answers, evidence, conclusions, deliberation by the panel, and then reading of the verdict.Keywords: domestic violence; case resolution; Palembang Religious Court.